1996
DOI: 10.1074/jbc.271.44.27818
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation Defect in Lec1 Chinese Hamster Ovary Mutant Is Due to a Point Mutation in N-Acetylglucosaminyltransferase I Gene

Abstract: The Lec1 Chinese hamster ovary (CHO) mutant is a leuco-phytohemagglutinin resistant cell line unable to synthesize complex and hybrid N-glycans due to the lack of N-acetylglucosaminyltransferase I (GnTI) activity. Here we have identified the lec1 mutation. ) are correctly localized to the Golgi apparatus, indicating that the inactive GnTI molecules are sufficiently well folded for efficient transport from the endoplasmic reticulum. These results demonstrate that the lec1 mutation is a point mutation and that C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 34 publications
2
38
0
Order By: Relevance
“…Previously, it has been shown that a point mutation in the coding region of N-acetylglucosaminyltransferase I and V leads into the glycosylation defect in Lec1 and Lec4A cells, respectively (39,40). In carbohydrate-deficient glycoprotein syndrome type II, a point mutation was discovered in the nucleotide sequence encoding the catalytic domain of ␤-1,2-Nacetylglucosaminyltransferase II (41).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been shown that a point mutation in the coding region of N-acetylglucosaminyltransferase I and V leads into the glycosylation defect in Lec1 and Lec4A cells, respectively (39,40). In carbohydrate-deficient glycoprotein syndrome type II, a point mutation was discovered in the nucleotide sequence encoding the catalytic domain of ␤-1,2-Nacetylglucosaminyltransferase II (41).…”
Section: Discussionmentioning
confidence: 99%
“…To confirm that the inability of influenza virus to infect Lec1 cells was solely due to the presence of terminal N-linked carbohydrate, we transiently expressed the wild-type GnT1 gene (17) in Lec1 cells and examined virus infection. GnT1 expression was confirmed by the ability of transfected cells to bind L-PHA.…”
Section: Influenza Virus Infection Of Lec1 Cells Is Rescued By Expresmentioning
confidence: 99%
“…Lec1 cells were isolated by selection of CHO cells with the cytotoxic lectin Phaseolus vulgaris leukoagglutinin (L-PHA) (15), which binds to complex carbohydrate structures, such as tri-and tetraantennary glycopeptides containing outer galactose residues and an ␣-linked mannose residue substituted at positions C-2 and C-6 (16). Lec1 cells have been characterized as having a defect in the N-acetylglucosaminyltransferase I (GnT1) gene (17,18). As such, they are unable to synthesize mature N-glycans containing terminal branches ending with galactose and sialic acid due to the absence of the glycosyltransferase GnT1, the outcome of which is that they are deficient in receptor sialo-Nglycans (19), although they are not deficient in glycosphingolipids and should not be deficient in O-linked glycans (P. Stanley, personal communication).…”
mentioning
confidence: 99%
“…The Mgat1 gene encoding GlcNAcT1 adds GlcNAc to high-mannose sites (Schachter, 2010); an essential early step in producing all complex and hybrid N-glycans (Pownall et al, 1992;Ye and Marth, 2004). Thus, MGAT1 generates the entire repertoire of polymeric branched Nglycans destined for secretion or presentation on the cell surface (Puthalakath et al, 1996); and Mgat1 null mutants, containing high mannose in place of complex/hybrid N-glycans, are the earliest Nglycan pathway block available to study N-glycosylation requirements in neural development (Schachter and Boulianne, 2011). Mouse Mgat1 knockouts are lethal at embryonic day (E) 9.5, but conditional mutants show movement defects, tremors, paralysis and early death characteristic of neurodevelopmental impairments (Campbell et al, 1995;Grasa et al, 2012;Shi et al, 2004;Ye and Marth, 2004).…”
Section: Introductionmentioning
confidence: 99%